196k views
4 votes
Please help me I can’t figure out the answer

Please help me I can’t figure out the answer-example-1

1 Answer

5 votes

9514 1404 393

Answer:

(x, y) = (5, 6)

Explanation:

When you have two equations in "y = ..." form, you can equate the two expressions for y.

y = 2x -4

y = x +1 . . . . . both are given

__

Equating y to itself, we have ...

y = y

2x -4 = x +1 . . . . . substitute the given expressions

x = 5 . . . . . . . . . . add 4-x to both sides

Then either equation can be used to find y:

y = x +1 = 5 +1 = 6

The solution is (x, y) = (5, 6).

User Chandra Shekhar
by
3.9k points